Multidrug-resistant tuberculosis transmission among middle school students in Zhejiang Province, China - Yu Zhang; Lin Zhou; Zheng-Wei Liu; Cheng-Liang Chai; Xiao-Meng Wang; Jian-Min Jiang; Song-Hua Chen (Infectious Diseases of Poverty, 2020)
Abstract Background Despite significant advancements in the treatment and diagnosis of tuberculosis (TB) over the past decade, drug-resistant TB remains an increasing threat to public health. TB outbreaks are most commonly reported in schools considering the delay in TB diagnosis, sustained contact, and overcrowding observed in schools. This report describes multidrug-resistant TB (MDR-TB) transmission in a school in Zhejiang Province. We aimed to raise awareness regarding MDR-TB transmission among students. Case presentation The index patient was a 16-year-old girl in the second year of junior middle school in Zhejiang Province, China, who had been experiencing persistent cough and expectoration for 37 days since 1 March 2014. She tested positive for smear pulmonary and extrapulmonary TB on 8 April 2014 and was subsequently diagnosed with MDR-TB on 1 May 2014. However, the patient was resistant to isoniazid, rifampicin, ethambutol, and streptomycin. Thus, she was suspended from school for anti-TB treatment. All 54 students who were in close contact with the index patient in the same class were screened, and 5 tested positive on the tuberculin skin test. Their exposure time to the index patient was approximately 37 days. Three classmates were subsequently diagnosed with MDR-TB, with similar resistance profiles nearly two years later. Their average discovery delay was 55 days. These three classmates were also suspended from school for anti-TB treatment. During the treatment period, four students visited the local TB-designated hospital for further consultation every month and were followed up once a month by the local community health service center until they were completely cured. Conclusions Discovery delay for an index patient played a primary role in MDR-TB transmission inside the school. To immediately detect TB, morning examinations in schools should be performed. TB trackers and case managers should work closely with public health workers and physicians in cases of TB outbreaks or transmissions involving students. Moreover, individuals who are in close contact with MDR-TB patients should undergo careful clinical follow-up for at least two years. Implementing a joint examination strategy to ensure early detection, diagnosis, and treatment of MDR-TB transmission is recommended.